2015
DOI: 10.1681/asn.2015060617
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Aging in ESRD: Structural, Hemodynamic, and Mortality Implications

Abstract: Aging incurs aortic stiffening and dilation, but these changes are less pronounced in peripheral arteries, resulting in stiffness and geometry gradients influencing progression of the forward and reflected pressure waves. Because premature arterial aging is observed in ESRD, we determined the respective roles of stiffness and aortic geometry gradients in 73 controls and 156 patients on hemodialysis. We measured aortic pulse wave velocity (PWV) and brachial PWV to evaluate the stiffness gradient [(brachial PWV/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 46 publications
1
61
0
4
Order By: Relevance
“…Cardiovascular disease is a major cause of morbidity and mortality in patients with chronic kidney disease (CKD) or end-stage renal disease (ESRD) [13-15]. Premature aging and early vascular aging is the most characteristic arterial change observed in ESRD [14, 15] (Fig.…”
Section: Arterial Stiffness In End-stage Renal Disease (Chronic Kidnementioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular disease is a major cause of morbidity and mortality in patients with chronic kidney disease (CKD) or end-stage renal disease (ESRD) [13-15]. Premature aging and early vascular aging is the most characteristic arterial change observed in ESRD [14, 15] (Fig.…”
Section: Arterial Stiffness In End-stage Renal Disease (Chronic Kidnementioning
confidence: 99%
“…Premature aging and early vascular aging is the most characteristic arterial change observed in ESRD [14, 15] (Fig. 1).…”
Section: Arterial Stiffness In End-stage Renal Disease (Chronic Kidnementioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper by London et al (25) has added to the field by suggesting that, in addition to assessing aortic stiffness in patients with renal disease, aortic geometry may also provide valuable prognostic information. In patients with ESRD established on hemodialysis, London et al (25) found that, such as for PWV, aortic bifurcation diameter (and aortic taper-defined as ascending aorta-to-aorta bifurcation diameters ratio) independently predicted all-cause and cardiovascular mortality.…”
mentioning
confidence: 99%
“…In patients with ESRD established on hemodialysis, London et al (25) found that, such as for PWV, aortic bifurcation diameter (and aortic taper-defined as ascending aorta-to-aorta bifurcation diameters ratio) independently predicted all-cause and cardiovascular mortality. Because those with earlier stages of CKD are more likely to die from CVD than reach ESRD, they should certainly be the focus of future studies.…”
mentioning
confidence: 99%